What Is a Geriatrician? American Geriatrics Society and Association of Directors of Geriatric Academic Programs End‐of‐Training Entrustable Professional Activities for Geriatric Medicine. Issue 5 (20th April 2014) - Leipzig, Rosanne M.; Sauvigné, Karen; Granville, Lisa J.; Harper, G. Michael; Kirk, Lynne M.; Levine, Sharon A.; Mosqueda, Laura; Parks, Susan Mockus; Fernandez, Helen M.
<x xml:space="preserve">Abstract</x> Entrustable professional activities (EPAs) describe the core work that constitutes a discipline's specific expertise and provide the framework for faculty to perform meaningful assessment of geriatric fellows. This article describes the collaborative process of developing the end‐of‐training American Geriatrics Society (AGS) and Association of Directors of Geriatric Academic Programs (ADGAP) EPAs for Geriatric Medicine (AGS/ADGAP EPAs). The geriatrics EPAs describes a geriatrician's fundamental expertise and how geriatricians differ from general internists and family practitioners who care for older adults.